Effective, but not all the time: Experimental evidence on the effectiveness of a code of ethics' design - Peter Kotzian; Thomas Stöber; Barbara E. Weißenberger; Florian Hoos (Business and Society Review, 2021)
Relations between society and business are increasingly characterized by the societal demand for compliance with ethical standards. Companies are held responsible for behavior of their employees, which increases the demand for effective internal governance. To assure compliance, many companies enact codes of ethics. Despite a common core of ethical standards, codes differ considerably in formal design elements. Albeit theory suggests that a code's formal design, that is, how a code's content is presented, affects its behavioral impact, there is little research on this issue. Addressing this research gap, we conducted a between-subjects experiment (factorial survey) in which we manipulated design elements of codes and examined how these elements affect behavioral intentions in various business situations. Holding the code's content constant, we manipulated its tone (positive vs. negative) and whether it was signed by the company's executive board (with vs. without signature). Our results indicate that the effectiveness of a code can be improved by using signed codes, while there is no effect for a code's tone. Our paper contributes designing internal governance in two ways: by giving experimental evidence on the relevance of a code's formal design and by providing practical guidance how to increase code effectiveness.
Keywords: 330; code of ethics; corporate compliance; ethical decision making